2014
DOI: 10.1088/1741-2560/11/3/036008
|View full text |Cite
|
Sign up to set email alerts
|

P300 speller BCI with a mobile EEG system: comparison to a traditional amplifier

Abstract: We conclude that efficient P300 spelling with a small, lightweight and quick to set up mobile EEG amplifier is possible. This technology facilitates the transfer of BCI applications from the laboratory to natural daily life environments, one of the key challenges in current BCI research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 36 publications
8
104
0
Order By: Relevance
“…For example, a recent BCI study directly compared wireless mobile and traditional fixed amplifiers using a simple lab based task. Results revealed a high degree of correlation in the amplitude and topography of P300 effects across systems, suggesting that it is now possible to capture comparable EEG data using mobile amplifiers (De Vos et al, 2014a). Whilst this study is important as a test of the basic validity of the mobile equipment, demonstrating that a known neural signal can be accurately measured, it does not address a key requirement: the ability to record clear signals during motion.…”
Section: Toward a Mobile Cognition Approachmentioning
confidence: 95%
“…For example, a recent BCI study directly compared wireless mobile and traditional fixed amplifiers using a simple lab based task. Results revealed a high degree of correlation in the amplitude and topography of P300 effects across systems, suggesting that it is now possible to capture comparable EEG data using mobile amplifiers (De Vos et al, 2014a). Whilst this study is important as a test of the basic validity of the mobile equipment, demonstrating that a known neural signal can be accurately measured, it does not address a key requirement: the ability to record clear signals during motion.…”
Section: Toward a Mobile Cognition Approachmentioning
confidence: 95%
“…The EPOC system has also been successfully used to measure the response of cortical response to auditory stimulation (evoked potential, P3 component) [2,3] and visual stimulation [3,4]. The results indicated a high accuracy for ERP (event-related potential or evoked potential) peaks, ie.…”
Section: Emotiv Epoc Headset In Human-computer Interactionmentioning
confidence: 99%
“…Liao et al [4] proposed a design method for the 16-channel EEG measurement system utilizing dry spring-loaded sensors, a Bluetooth-based acquisition system, and a size-adjustable wearable soft cap. Vos et al [5] demonstrated an efficient low-cost mobile EEG system that utilizes a P300-based speller for wireless BCI.…”
Section: Introductionmentioning
confidence: 99%